Retail Business Competition System on Halal Business Compliance: A Comparative Study of Indomaret Fresh and Surya Mart Ponorogo (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2025)
ABSTRACT Purpose – Competition in the retail industry can be seen from various angles. This competition can be observed between contemporary and conventional traders. In business competition in the retail business, it must also comply with sharia provisions, especially on the halal side, because many of the people in the Ponorogo area are Muslims and are famous as a city of students, therefore the business operations of Indomaret Retail and Surya Mart Supermarket in Ponorogo as well as a review in halal retail business compliance. Methods – The method used is qualitative with collection techniques used, including observation, in-depth non-structural interviews, and documentation. Findings – The results of this study illustrate comparatively, on the business competition of Indomaret Fresh Ponorogo and Surya Mart. Indomaret Fresh Ponorogo emphasizes coordination between branches related to product determination with a focus on direct and online promotion, while emphasizing price transparency to build consumer confidence. Meanwhile, Surya Mart affirms its commitment to Islamic values by rejecting non-halal products, emphasizing honesty and competitive prices, and affirming fairness in price determination based on sharia values. Originality – Although their approaches are different, both aim to build consumer trust by the company values they set, so that Surya Mart not only optimizes the value of the company, but they are more compliant with sharia values, especially in halal business complianceKeywords: Retail, Business Competition, Halal Business Compliance